An audit of echocardiograms in acute left ventricular failure. Issue 842 (December 1995) - Morgan, R.; King, D.
Abstract : All patients with heart failure should have an echocardiogram to establish a diagnosis, both to aid treatment as well as for prognostic reasons. An audit of 100 case notes of patients admitted with acute left ventricular failure over a 12-month period found that 26 patients had not had an echocardiogram. Of the 74 who did have an echocardiogram 68 patients had reduced systolic function (mean ejection fraction 42%). Almost all (93%) were commenced on an angiotension-converting enzyme (ACE) inhibitor. Those who did not receive an ACE inhibitor had no contraindications to these drugs. Seventeen patients had a confirmed myocardial infarction. Of these, 11 had an echocardiogram and 10 were discharged home on an ACE inhibitor. Despite appropriate indications some patients are deprived of echocardiography as well as the benefits of ACE inhibitors.